Auxin transport and conjugation caught together - Ružicka, Kamil; Hejátko, Jan (Journal of experimental botany, 2017)
This article comments on: Kong Q, Ma W, Yang H, Ma G, Mantyla JJ, Benning C. 2017. The Arabidopsis WRINKLED1 transcription factor affects auxin homeostasis in roots. Journal of Experimental Botany 68, 4627–4634.
Keywords: membránové transportní proteiny; Biological Transport; GH3; PIN expression; Indoleacetic Acids; biologický transport; Membrane Transport Proteins; endoplasmic reticulum; transcriptional regulation; Arabidopsis Proteins; IAA conjugation; Gene Expression Regulation, Plant; polar auxin transport; kyseliny indoloctové; regulace genové exprese u rostlin; Arabidopsis; proteiny huseníčku